Super-high-resolution aerial imagery, digital surface models and 3D point clouds of Trail Valley Creek, Canada - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the MOSES airborne campaign led by the Alfred Wegener Institute in 2018, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates eight data subsets of Trail Valley Creek, Canada, covering approximately 150 km². All images were collected on 22 August 2018.
Keywords: Arctic Landscape Dynamics; Canada; Digital Surface Model; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion